1989 Proceedings / International Trade and Finance Association - Fatemi Khosrow; Mann Catherine; Laredo State University (1989)
Forward, Introduction, Whither U.S. Trade Policy, International Trade Issues, Foreign Exchange Rates, Multinational Coorporations, Regional and National Studies.